The Oral Microbiome Bank of China - Peng Xian; Zhou Xuedong; Xu Xin; Li Yuqing; Li Yan; Li Jiyao; Su Xiaoquan; Huang Shi; Xu Jian; Liao Ga (Nature Publishing Group, 2018)
Microbiology: A census of oral ecosystems A new resource for consolidating oral microbiome data will help researchers explore the relationship between these commensal communities and the health of their hosts. Numerous studies have highlighted apparent connections between alterations in the microbial communities within the human mouth and medical conditions including diabetes and cancer. A recent article from researchers led by Liao Ga at Sichuan University describes the launch of the Oral Microbiome Bank of China, an effort to study such connections by profiling specimens from individuals from across the country. The database currently houses detailed information on 289 bacterial strains and the samples from which they were obtained. The authors are now looking to analyze these data to gain insights into the structure and function of oral ecosystems, and to further expand this database as a resource for Chinese microbiome research.